Leveraging the Camino de Santiago: promoting intentional reflection and group cohesion during study abroad. Issue 2 (4th March 2022) - Knouse, Stephanie M.
ABSTRACT: The present investigation describes how one semester-long study abroad (SA) program leveraged a group excursion at the beginning of the term to promote intentional reflection, a critical skill to process 'disorienting dilemmas' often encountered abroad. The excursion took place on the Camino de Santiago, or 'the Way of Saint James', a well-known pilgrimage in northern Spain. While multitudes of pilgrims have traveled the Camino for over a millennium, it has rarely been featured in educational research. Eighteen women undergraduates from a US institution participated in a two-day hike on the Camino two weeks into their program, and completed a variety of reflection activities in situ . Data collected immediately after the experience and three months later were analyzed quantitatively and qualitatively. Results suggest that students' experiences on the Camino – coupled with intentional reflection exercises – helped them gain confidence in the early weeks of their SA semester, and served as a catalyst for camaraderie among participants. Pedagogical and programmatic recommendations of how to structure intentional reflection, especially at the beginning of a SA program, are offered. The article concludes with a call to action to further investigate the role of intensive intentional reflection, especially at the onset of SA.